The secretory pathway: exploring yeast diversity. Issue 6 (12th April 2013) - Delic, Marizela; Valli, Minoska; Graf, Alexandra B.; Pfeffer, Martin; Mattanovich, Diethard; Gasser, Brigitte
Abstract Protein secretion is an essential process for living organisms. In eukaryotes, this encompasses numerous steps mediated by several hundred cellular proteins. The core functions of translocation through the endoplasmic reticulum membrane, primary glycosylation, folding and quality control, and vesicle‐mediated secretion are similar from yeasts to higher eukaryotes. However, recent research has revealed significant functional differences between yeasts and mammalian cells, and even among diverse yeast species. This review provides a current overview of the canonical protein secretion pathway in the model yeast Saccharomyces cerevisiae, highlighting differences to mammalian cells as well as currently unresolved questions, and provides a genomic comparison of the S. cerevisiae pathway to seven other yeast species where secretion has been investigated due to their attraction as protein production platforms, or for their relevance as pathogens. The analysis of Candida albicans, Candida glabrata, Kluyveromyces lactis, Pichia pastoris, Hansenula polymorpha, Yarrowia lipolytica, and Schizosaccharomyces pombe reveals that many – but not all – secretion steps are more redundant in S. cerevisiae due to duplicated genes, while some processes are even absent in this model yeast. Recent research obviates that even where homologous genes are present, small differences in protein sequence and/or differences in the regulation of gene expression may lead to quite different protein secretion phenotypes.